FBXW5 promotes tumorigenesis and metastasis in gastric cancer via activation of the FAK-src signaling pathway - Yeo, Mei Shi; Subhash, Vinod Vijay; Suda, Kazuto; Balcıoğlu, Hayri Emrah; Zhou, Siqin; Thuya, Win Lwin; Loh, Xin Yi; Jammula, Sriganesh; Peethala, Praveen C.; Tan, Shi Hui; Xie, Chen; Wong, Foong Ying; et al. (Cancers, 2019)
F-box/WD repeat-containing protein 5 (FBXW5) is a member of the FBXW subclass of F-box proteins. Despite its known function as a component of the Skp1-Cullin-F-box (SCF) ubiquitin ligase complex, the role of FBXW5 in gastric cancer tumorigenesis and metastasis has not been investigated. The present study investigates the role of FBXW5 in tumorigenesis and metastasis, as well as the regulation of key signaling pathways in gastric cancer; using in-vitro FBXW5 knockdown/overexpression cell line and in-vivo models. In-vitro knockdown of FBXW5 results in a decrease in cell proliferation and cell cycle progression, with a concomitant increase in cell apoptosis and caspase-3 activity. Furthermore, knockdown of FBXW5 also leads to a down regulation in cell migration and adhesion, characterized by a reduction in actin polymerization, focal adhesion turnover and traction forces. This study also delineates the mechanistic role of FBXW5 in oncogenic signaling as its inhibition down regulates RhoA-ROCK 1 (Rho-associated protein kinase 1) and focal adhesion kinase (FAK) signaling cascades. Overexpression of FBXW5 promotes in-vivo tumor growth, whereas its inhibition down regulates in-vivo tumor metastasis. When considered together, our study identifies the novel oncogenic role of FBXW5 in gastric cancer and draws further interest regarding its clinical utility as a potential therapeutic target.
CRIS-Team Scopus Importer:2024-02-19
Keywords: FAK-Src signaling; FBXW5 (F-box/WD repeat-containing protein 5); Metastasis; Tumorigenesis